Response of Staphylococcus aureus to combination of virulent bacteriophage vB_SauM-515A1 and linezolid - Abdraimova, Narina K.; Shitikov, Egor A.; Bespiatykh, Dmitry A.; Gorodnichev, Roman B.; Klimina, Ksenia M.; Veselovsky, Vladimir A.; Boldyreva, Daria I.; Bogdanova, Alexandra S.; Klinov, Dmitry V.; Kornienko, Maria A. (Frontiers in Microbiology, 2024)
The combined use of lytic bacteriophages with antibiotics is currently being explored as a strategy to enhance the effectiveness of infectious disease therapies, including those caused by Staphylococcus aureus. In this study, we investigated the synergistic potential of bacteriophage vB_SauM-515A1 (Herelleviridae family) and the first-line antibiotic linezolid against the methicillin-resistant S. aureus strain SA0413Rev. A checkerboard assay revealed a significant synergistic effect against planktonic cells (FIC = 0.225): a combination of 1/8 MIC of linezolid and 0.01 MOI of the bacteriophage completely inhibited bacterial growth. However, the impact on biofilm-associated cells depended on the treatment sequence. Sequential administration resulted in antagonism, while simultaneous application demonstrated a synergistic effect, as confirmed through scanning electron microscopy. Transcriptomic analysis of S. aureus SA0413Rev under the combined influence of linezolid (1/4 MIC) and bacteriophage vB_SauM-515A1 (10 MOI) predominantly reflected changes associated with productive bacteriophage infection, including alterations in nucleotide metabolism, activation of prophage regions, and virulence factors. Furthermore, both agents affected energy and carbon metabolism. These findings contribute to the development of combination therapy approaches for infections caused by S. aureus and highlight the importance of optimizing treatment conditions for maximal therapeutic efficacy.